Experimental Study of Spray Characteristics of Kerosene-Ethanol Blends from a Pressure-Swirl Nozzle - Tao Zhang; Bo Dong; Xun Zhou; Linan Guan; Weizhong Li; Shengqi Zhou (International Journal of Aerospace Engineering)
Partial replacement of kerosene by ethanol in a gas turbine is regarded as a good way to improve the spray quality and reduce the fossil energy consumption. The present work is aimed at studying the spray characteristics of kerosene-ethanol blends discharging from a pressure-swirl nozzle. The spray cone angle, discharge coefficient, breakup length, and velocity distribution are obtained by particle image velocimetry, while droplet size is acquired by particle/droplet imaging analysis. Kerosene, E10 (10% ethanol, 90% kerosene), E20 (20% ethanol, 80% kerosene), and E30 (30% ethanol, 70% kerosene) have been considered under the injection pressure of 0.1–1 MPa. The results show that as injection pressure is increased, the discharge coefficient and breakup length decrease, while the spray cone angle, drop size, and spray velocity increase. Meanwhile, the drop size decreases and the spray velocity increases with ethanol concentration when the injection pressure is lower than 0.8 MPa. However, the spray characteristics are not affected obviously by the ethanol concentration when the injection pressure exceeds 0.8 MPa. A relation to breakup length for kerosene-ethanol blends is obtained. The findings demonstrate that the adding of ethanol into kerosene can promote atomization performance.